Dementia care in the Danube Region. A multi-national expert survey - Mehrabian S (Dove Medical Press, 2019)
Shima Mehrabian,1 Larissa Schwarzkopf,2 Stefanie Auer,3 Iva Holmerova,4 Milica G Kramberger,5 Marina Boban,6 Elka Stefanova,7 Catalina Tudose,8 Natalia Bachinskaya,9 Tibor Kovács,10 Petr Koranda,11 Todor Kunchev,1 Latchezar Traykov,1 Janine Diehl-Schmid,12 Katrina Milecka,12 Alexander Kurz12On behalf of the Danubian Network for Dementia Education Care (DANDEC) Consortium1UH “Alexandrovska”, Department of Neurology, Medical University Sofia, Sofia, Bulgaria; 2Helmholtz-Centre Munich, Deutsches Forschungszentrum für Gesundheit und Umwelt (GmbH), Munich, Germany; 3Department for Clinical Neurosciences and Preventive Medicine, Danube University Krems, Krems, Austria; 4CELLO Faculty of Humanities, Charles University, Prague, the Czech Republic; 5University of Ljubljana, Department of Neurology, Ljubljana, Slovenia; 6University of Zagreb, Department of Cognitive Neurology, Zagreb, Croatia; 7School of Medicine, University of Belgrade, Neurology Clinic, Belgrade, Serbia; 8University of Medicine and Pharmacy Carol Davila, Department of Clinical Neurosciences, Bucharest, Romania; 9Acacdemy of Medical Sciences Kiev, Department of clinical physiology and pathology of the central nervous system, Kiev, the Ukraine; 10Department of Neurology, Semmelweis University, Budapest, Hungary; 11MEDIWARE corp., Prague, the Czech Republic; 12Department of Psychiatry and Psychotherapy, Klinikum rechts der Isar, Technische Universität München, Munich, GermanyCorrespondence: Alexander KurzCentre for Cognitive Disorders at the Department of Psychiatry and Psychotherapy, Klinikum rechts der Isar; Technische Universität München, Ismaninger Strasse 22 Munich 81675, GermanyTel +49 894 140 4285Email a.kurz@tum.deBackground: Dementia is a particularly severe societal challenge in several countries of the Danube Region due to higher-than-average increment in population longevity, disproportionate increase of the old-age dependency ratio, and selective outward migration of health care professionals. A survey was conducted among dementia experts to obtain a deeper understanding of the dementia care structures and services in this geographical area, and to identify the educational needs of health care professionals, and the availability of assistive technology.Subjects and methods: A standardized questionnaire was sent out to 15 leading dementia experts/clinicians in 10 Danube Region countries inquiring about professional groups involved in dementia care, availability and reimbursement of services, inclusion of dementia in professional education and training, acceptability of Internet-based education, and availability of assistive technology. The authors are the survey respondents.Results: The majority of individuals with dementia receive care in the community rather than in institutions. The roles of medical specialties are disparate. General practitioners usually identify dementia symptoms while specialists contribute most to clinical diagnosis and treatment. Health care professionals, particularly those who work closely with patients and carers, have limited access to dementia-specific education and training. The greatest need for dementia-specific education is seen for general practitioners and nurses. An Internet-based education and skill-building program is considered to be equivalent to traditional face-to-face but offer advantages in terms of convenience of access. Assistive technology is available in countries of the Danube Region but is significantly underused.Conclusion: Dementia care in the Danube Region can be improved by an educational and skill-building program for health care professionals who work in the frontline of dementia care. Such a program should also attempt to enhance interdisciplinary and intersectorial collaboration, to intensify the interaction between primary care and specialists, and to promote the implementation of assistive technology.Keywords: dementia, Danube Region, expert survey, dementia care structures, education, assistive technology